Effect of Carbon and Oxygen on the Densification and Microstructure of Hot Pressed Zirconium Diboride. Issue 11 (30th August 2013) - Harrington, Gregory J. K.; Hilmas, Greg E.; Fahrenholtz, William G.
Abstract : The role of carbon additions and oxygen content on the densification of zirconium diboride (ZrB2 ) was studied. ZrB2 with up to 1 wt% added carbon was hot pressed at temperatures of 2000°C and 2100°C. Nominally pure ZrB2 hot pressed at 2100°C achieved relative densities >95.5%. Carbon and oxygen analysis indicate that oxygen removal was facilitated by the reduction of oxides with carbon or the removal of boria (B2 O3 ) as a vapor. Therefore, by removing oxides from the particle surfaces, carbon additions of ≥0.5 wt% enabled densification to proceed to >96.5% of theoretical at 2000°C. Raman spectroscopy revealed the formation of boron carbide (B4.3 C) in specimens with carbon additions of ≥0.75 wt%. The formation of B4.3 C was eliminated via a 1 wt% addition of zirconium hydride (ZrH2 ), as a source of zirconium, resulting in the formation of carbon as the only residual second phase. Grain sizes were in the range of 7–10 μm (2000°C) and 12–16 μm (2100°C) and only appeared to be controlled by temperature, as no trends due to the evaluated carbon or oxygen contents were observed.